Tradition and innovation in Aratus Phaenomena. The example of the asterism of the Bears (Argos, 2022)
Through the copy and reinterpretation of Phaenomena, the most complete stellar cataloging work in the West begins. But beyond the astronomical matrix of the poem, the mythical reworking carried out by Aratus evidences an effort of cultural assimilation and ordering of the celestial vault. The sky of the third century B.C. appears as a semiotic, poetic and divulgable living matter, arranged as a λóγος for the well-being of man, who is a potential reader of signs that allows him to intervene in the world. In this work we focus on the passage of the Bears (vv. 26-44) as a paradigm of analysis.
Keywords: Hellenistic Astronomy; Mythography; Aratus; Bears; Catasterisms